Numerical investigation of T-Foil hybrid control strategy for ship motion reduction in head seas. (1st December 2020) - Jiang, Yichen; Bai, Junyu; Sun, Yuan; Sun, Yifang; Zong, Zhi
Abstract: An active control T-foil can significantly reduce the vertical motions of high-speed ships. In this paper, a hybrid control method is proposed to control the T-foil. The reduction effects of the method, along with passive, linear and step controls, are numerically investigated. A numerical model is introduced firstly. Then the numerical predictions are compared with experimental measurements to validate the numerical model. Finally, the heave, pitch and local acceleration of the Wigley model III are predicted under four control strategies at two forward speeds (Fr = 0.3, 0.5). Based on the percentage reduction of vertical motions, the local velocity signal performs better than the pitch velocity signal. The reduction effect of the linear control is critical when the encounter frequency is high but limited when the encounter frequency becomes lower. The step control has the best effect at Fr = 0.3, but it aggravates the vertical motions in some cases at Fr = 0.5. The hybrid control offers the advantages of both linear and step controls and significantly reduces the vertical motions. The performance of the method is dominated by a parameter, CI, which makes the strategy take effect more stable and fit diverse sea conditions. Highlights: The hybrid control strategy is proposed to control the T-foil, which can significantly reduce the vertical motions. A time domain numerical model of an active control T-foil is proposed to predict the motions of a ship with a T-foil. The time histories of moments and flap angles of the T-foil is presented to study the mechanism of the control strategies.